The Gambia Impact Evaluation Baseline Report : Health System - World Bank Group (World Bank, Washington, DC, 2015)
The Government of The Gambia is implementing the Maternal and Child Nutrition and Health Results Project (MCNHRP) to increase the utilization of community nutrition and primary maternal and child health services. In collaboration with the Government, the World Bank is conducting an impact evaluation (IE) to assess the impact of the project on key aspects of maternal and child nutrition and health. The baseline survey for the MCNHRP IE took place between November 2014 and February 2015. It collected both quantitative and qualitative data and covered three regions: Central River Region (CRR), North Bank Region West (NBR-W) and Upper River Region (URR). Its purpose was to establish a baseline against which project performance will be assessed in the future. This technical brief summarizes the findings of the baseline report related to use of family planning.